Religious Beliefs, Possession States, and Spirits: Three Case Studies from Sri Lanka - Raveen Hanwella; Varuni de Silva; Alam Yoosuf; Sanjeewani Karunaratne; Pushpa de Silva (Case Reports in Psychiatry)
We describe three patients from different religious backgrounds in Sri Lanka whose possession states were strongly influenced by their religious beliefs. Patient A was a Buddhist who claimed to have special powers given by a local deity named Paththini. Patient B was a Catholic who experienced spirits around her whom she believed were sent by Satan. Patient C was a Muslim and believed she was possessed by spirits. The religious beliefs also influenced the help-seeking behaviour and the rituals or treatments to which they responded.